GRAFOS EXPANSORES EN CRIPTOGRAFÍA - DARÍO ALEJANDRO GARCÍA (Revista Ingeniería, Matemáticas y Ciencias de la Información)
What is the surest way to keep a message secret? The obvious answer to this question is, of course, to give the messageuniquely and directly to the recipient. But, what happens if it is necessary to transmit the message through a medium in thepresence of third parties? How can we ensure that the recipient receives the message and, at the same time, preventanyone else from discovering it?